2015
DOI: 10.1080/13548506.2015.1111394
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and carers’ views and expectations about intensive management for moderate rheumatoid arthritis: a qualitative study

Abstract: Intensive management for rheumatoid arthritis (RA) involves frequent hospital visits and adjusted doses or combinations of medication. Research is currently underway to test whether or not intensive management strategies are valuable in moderately active disease, however, patient views on intensive management in this disease group are unknown. The objectives of this study were to explore the views and expectations of patients with moderately active RA and of carers of patients with moderately active RA. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…6,7 However, studies evaluating their role in RA are scarce. 8,9 One study in patients with RA found that patients were inclined to significantly underscore their level of pain, compared with their carers. 8 This could affect the rheumatologist's decision to adjust the management strategy and undermine efforts to achieve optimal results, unless further information is obtained from the carer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 However, studies evaluating their role in RA are scarce. 8,9 One study in patients with RA found that patients were inclined to significantly underscore their level of pain, compared with their carers. 8 This could affect the rheumatologist's decision to adjust the management strategy and undermine efforts to achieve optimal results, unless further information is obtained from the carer.…”
Section: Introductionmentioning
confidence: 99%
“…8 Another study highlighted carers may help to illuminate factors that patients may not consider themselves. 9 For instance, patients were more likely to consider intensive management acceptable if their previous treatments had failed. However, carers took into consideration the patient's past experiences of side effects, treatment duration, and response to current treatment (both emotionally and physically).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidance and examples of how to involve patients and the public in research have been published . In Academic Rheumatology at King's College London, we have been involving patients (as ‘patient experts’) for over a decade in teaching, research and co‐authoring publications …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In Academic Rheumatology at King's College London, we have been involving patients (as 'patient experts') for over a decade in teaching, research and co-authoring publications. [7][8][9][10][11][12][13][14][15][16][17] In clinical practice, the traditional paternalistic attitude of 'Doctor knows best' had been the status quo for many years and quality of care equated to good clinical care. The latter has since changed to include dimensions such as safety, clinical effectiveness and patientcentredness, and is now embedded in the UK National Health Service (NHS) constitution.…”
Section: Introductionmentioning
confidence: 99%